Outdoor Performance Characterization of the Poly-crystalline Silicon Solar Module (Journal of Science Foundation, 2018)
The outdoor performance characterization of the poly-crystalline silicon solar PV module was studied. Daily solar illumination data were measured using two pyranometers and analyzed together with the module output power. The present paper reports the temperature dependencies of full-spectrum photovoltaic parameters for poly-crystalline PV module. The measurements were performed under outdoor environment conditions. The most interesting feature that was observed for these devices is that above a cell temperature of 20 0C the positive temperature coefficient observed for the short-circuit current exceeds in magnitude the negative temperature coefficient that was found for the open-circuit voltage. This means that, unlike the situation for conventional PV module, these cells actually exhibit decrease in efficiency with increasing temperatureJournal of Science Foundation 2018;16(1):13-19